Occurrence of the greenhouse camel cricket Tachycines asynamorus Adelung, 1902 (Orthoptera: Rhaphidophoridae) in Poland - Żurawlew, Przemysław; Rozwałka, Robert; Brodacki, Michał (Muzeum i Instytut Zoologii Polskiej Akademii Nauk, 2022)
The greenhouse camel cricket Tachycines asynamorus is an insect of the order Orthoptera, native to Eastern Asia. It was introduced to Europe and North America at the end of the 19th century, probably along with exotic plants imported to botanical gardens, orangeries, and horticultural farms. In the climatic conditions of Central and Northern Europe this insect is exclusively synanthropic, occurring mainly in greenhouses, hothouses, and other permanently heated rooms with high humidity. In Poland, the species has been reported in 24 sites since the beginning of the 20th century. No specific information confirming its occurrence in the country after 1984 has been found in the literature. The search for the greenhouse camel cricket conducted by the authors, along with responses to surveys sent out to scientific institutions and naturalists requesting reports of sightings of the species, enabled us to establish that in 1991–2022 T. asynamorus occurred in Poland at 12 sites, mostly in greenhouses in botanical gardens and in aquaria and terraria buildings in zoological gardens. The presence of the species was confirmed at only one site known from the literature.
95–102 s.
Keywords: Ensifera; Diestrammena asynamora; synanthropic insect; distribution; Europe

Grasshoppers and crickets (Orthoptera), earwigs (Dermaptera) and cockroaches (Blattodea) of the Bory Tucholskie National Park (Poland) - Żurawlew, Przemysław; Grobelny, Seweryn; Brodacki, Michał; Wendzonka, Jacek (Muzeum i Instytut Zoologii Polskiej Akademii Nauk, 2022)
This paper presents the results of the study on grasshoppers and crickets (Orthoptera), earwigs (Dermaptera) and cockroaches (Blattodea) of the Bory Tucholskie National Park (=BTNP) (part of Tuchola Forest, northern Poland), conducted in the years 2001, 2013 and 2014. The insects were caught using Moericke traps at 9 sites, capturing respectively: 2001 – 11 ind., 2013 – 1115 ind. and 2014 – 228 ind. An additional visual record was made at the tenth site, where no traps were set. In total, 24 species of grasshoppers and crickets, 3 species of earwigs and 1 species of cockroach were recorded in the BTNP. Tettigonia cantans (Fuessly), Roeseliana roeselii (Hagenb.), Pholidoptera griseoaptera (Deg.), Chelidurella acanthopygia (Géné) and Labidura riparia (Pall.) were found for the first time within the whole Tuchola Forest. The research method used is noteworthy, as the capture of such a large number of orthopteroid insects in Moericke traps is rare in Poland.
25–34 s.
Keywords: Tuchola Forest; faunistic valorisation; insect trapping; Moericke traps; new records

The European mantis Mantis religiosa (Linnaeus, 1758) (Mantodea: Mantidae) in Poland – the present status and changes in range - Żurawlew, Przemysław; Kutera, Marcin; Orzechowski, Ryszard; Czyżewski, Szymon; Radzikowski, Paweł; Grobelny, Seweryn; Cymbała, Robert; Kolago, Grzegorz; Malkiewicz, Adam; Bury, Jarosław; Gwardjan, Mariusz; Sępioł, Bogusław; et al. (Muzeum i Instytut Zoologii Polskiej Akademii Nauk, 2022)
This paper presents the past and present occurence of Mantis religiosa in Poland and discusses range changes of this species during the last 100 years (1923–2021), basing on 2664 records, 2029 of these unpublished. Up to 1994, the species was restricted to a relatively small area in the south-eastern part of Poland (3.3% of the country's area). During 27 years (1995–2021), M. religiosa spread from there to the north, west and south, increasing its range more than 20 times, to 77% of Poland’s area. At present, only north-western part of the country and central part of mountainous belt in the south are not occupied or sparsely occupied by this species. The average annual increase in European mantis range in Poland in the years 2013–2021 was eight times faster than during the earlier period (1995–2012).
35–53 s.
Keywords: range expansion; population increase; expansive species; thermophilous insect; threats; protection